Structural modelling of influential factors affecting weight problem of primary school children in Selangor, Malaysia - Kheirollahpour, Maryam (2014)
The main objective of this study is to identify and develop a comprehensive model that can be used to estimate and evaluate the factors affecting weight problems in children. To fulfill such an aim Structural Equation Modeling (SEM) was applied, which is one of the complete and flexible technique for testing and estimating causal relations using a combination of statistical data and qualitative causal assumptions. The new structural model would present the overall relations among the factors that lead to weight gain in children. A growing body of research consistently points out that the socio-economic level of the family; parental feeding practice and physical activity play an important role in the weight status of children. The proposed models in this study explore the connection among these variables based on the definitions of the latent variables. Six structural models were tested to identify the direct and indirect relationship between the socio-economic factors and parental feeding practice, general level of physical activity and weight status of children. The structural model was assessed for convergent validity and construct reliability (internal consistency). Three hundred and ninety primary school children aged between seven (7) and nine (9) years old in Selangor and Kuala Lumpur, as well as their parents, participated as subjects in this study. Their Body Mass Index was measured while the data on parental feeding practice was obtained using a validated Malay version of the Children Feeding Practice Questionnaire CFPQ. Concerning the methodology of the current study, the statistical procedure applied was running SEM and Confirmatory Factor Analysis (CFA) to reveal the hidden (secondary) effect of socioeconomic factors on feeding practice, and, ultimately, the weight status of the children, and to assess the validity model. The structural model assessed in this study suggested that the socio-economic status of parents is directly related to feeding practice (coefficient=0.39, and p-value=0.031), as well as weight status of children (coefficient= -0.38, and p-value=0.001) and physical activity (coefficient=0.41, and p-value=0.001). In addition, the results indicate that parental feeding practice and physical activity are also directly related to the weight status of children (coefficient=0.36, and p-value=0.000), (coefficient= -0.29, and pvalue= 0.000), respectively. Moreover, the results suggest that parental feeding practice and physical activity are mediators in the structural model. In conclusion the model fit to the data well, and all the hypotheses linked to the conceptual framework were found to be significant.